2002
DOI: 10.1021/ol0259490
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Aspects of the Iodine(III)-Mediated Aziridination Reaction of Some Cyclic Allylic Carbamates

Abstract: [reaction: see text] The iodine(III)-mediated aziridination reaction of an indolyl-substituted carbamate requires a Rh(II) catalyst and proceeds by a metallonitrene intermediate. Stepwise addition across the indole pi-bond followed by Rh(II) detachment generates a metal-free zwitterion, which ultimately leads to the observed products. In contrast, intramolecular aziridination of several cycloalkenyl carbamates does not require a Rh(II) catalyst and occurs via an iminoiodinane intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(26 citation statements)
references
References 18 publications
1
23
1
1
Order By: Relevance
“…[35] Although further experiments extended the scope of the oxygen source to include alcohols, it was found that the high diastereoselectivity of the reaction was limited to the 3-indolyl carbamates; both 2-indolyl carbamates 35 and benzofuran derivatives 36 gave mixtures of cis and trans oxyamination products (Scheme 15). [36] Attempts to effect this transformation with other classes of alkene also failed, as the aziridine species could not be opened by oxygen nucleophiles under the reaction conditions.…”
Section: Rhodium-catalysed Reactionsmentioning
confidence: 99%
“…[35] Although further experiments extended the scope of the oxygen source to include alcohols, it was found that the high diastereoselectivity of the reaction was limited to the 3-indolyl carbamates; both 2-indolyl carbamates 35 and benzofuran derivatives 36 gave mixtures of cis and trans oxyamination products (Scheme 15). [36] Attempts to effect this transformation with other classes of alkene also failed, as the aziridine species could not be opened by oxygen nucleophiles under the reaction conditions.…”
Section: Rhodium-catalysed Reactionsmentioning
confidence: 99%
“…Padwa has shown that rhodium-catalyzed oxidation of indolyl carbamate 67 employing either PhI(OAc) 2 or PhI=O follows a path similar to that of the d-allal carbamate (Scheme 17.26) [95]. In principle, indole attack of the putative rhodium-nitrene generates zwitterion 68, which is trapped subsequently by an exogenous nucleophile.…”
Section: Carbamate Estersmentioning
confidence: 99%
“…We speculate that the rhodium-catalyzed oxidative cyclization of an indol-3-ylmethanol carbamate 7 (Scheme 9, 15 → 16), which was postulated to involve nucleophilic attack of the indole on the nitrogen of a rhodium-nitrene complex, is a partial precedent for the present conversion. …”
Section: Methodsmentioning
confidence: 97%